Group Decision Making Using Mean SAW Borda and Decision Maker-Based Criteria Weighting - Utomo, Pradityo; Amadi, Dwi Nor (Journal of Information System and Informatics, 2025)
In an organization, unfair decisions are often a problem. Therefore, this study creates a group decision-making model to optimize the achievement of fair decisions. This study combines the Mean and Simple Additive Weighting Borda (SAW Borda) methods. The combination of these methods is called Mean SAW Borda. The Mean calculation is used to obtain the average value of decision-makers. The mean value can be the weight of the group decision-making criteria. The weight is the reference for the SAW Borda calculation. This aims to optimize fair decisions. The SAW Borda calculation provides group decisions. This study uses data on the election of a university's head of the Informatics Engineering study program. In the study program, 24 decision-makers gave scores to choose the head of the study program. The Means SAW Borda method calculates the assessment, and the result is that A4 has the highest decision value (1923.26573). The results of the Mean SAW Borda method are the same as those of the conventional election. The conventional method chooses A4 to be the elected candidate. Based on these results, the Mean SAW Borda method can produce fair decisions and is agreed upon by decision-makers.